A construção da legislação cooperativista no Brasil e o pensamento dos autores nacionais, entre 1890 a 1964 - Silva, Carlos Alberto da (2021)
This thesis aims to investigate the concept, characterization and purpose (triad) of the cooperative society, in the federal legislation of the Old Republic (1890-1930), was Vargas (1930-45) and Democratic (1945-64) as well as the works of Brazilian cooperative authors published in this period. From the triad, it analyzes whether the objective of the society of people is restricted to the economic dimension or whether it is also attributed to a mainly social perspective. Simultaneously with the investigation of whether the cooperative society has a social function, the research identifies the main debates about the cooperative society that took place among the cooperativist authors in these periods and whether there was a connection with the triad in the delimited period. The research method is bibliographic and documentary, federal cooperative legislation of the period. The first period was marked by incipient cooperative legislation. At the legislative level, which concerns the triad, there was a timid characterization of the cooperative society. Six authors who lived in the Old Republic were studied, with emphasis on José Saturnino Britto who denounced the plural vote and defended the singular vote. Carvalho Mendonça, of these authors, is the only one to conceptualize a cooperative society. The Vargas era was marked by great legislative inflation, with emphasis on the first General Law of Cooperatives (22,239/32), the legal implementation of the professionalcooperative consortium and the first law that assigns the cooperative as a purpose, in addition to the economic dimension, as well. , the social (5,893/43). This standard contains both the concept and the characterization of the cooperative society. Among the cooperative authors, the debate was mainly located on the theme of the professional-cooperative consortium. In the doctrinal field, this period begins with Cunha Bueno's book, where he transcribes the draft law for the cooperative society and comments on some themes of his proposal for cooperative legislation. The main cooperative controversy of the Vargas Era was the proposal of Sarandy Raposo being incorporated into the legal system, ensuring unions exclusivity in the formation of a cooperative society. This organizational concept will find strong opposition from the group called Free Cooperativism. One of the members of this group is Luis Amaral, who claims that Sarandy's proposal has a Marxist hue. Fransciso Frola's work is also opposed to the professional-cooperative consortium. In this same tune, Fábio Luz Filho publishes several works, he opposed cooperative unionism. The jurist Mário Fonseca de Barros is the only author of this period who thoroughly analyzes and elaborates the concept of cooperative society. His work is entirely legal focused on this type of company. Ending this cycle Adolpho Gredilha, in addition to defending the repristination of the first General Law of Cooperatives, strives to build the concept of cooperative society. The third and last period, the Democratic one, was not published any new general norm of cooperativism. Writer Valdiki Moura publishes several works, and differs from Fábio Luz Filho on the most adequate legislation for cooperative society, synthetic or detailed. During this period, “The Cooperative School of São Paulo” was organized to promote cooperative education. Waldirio Bugarelli argued that cooperative doctrine has a social dimension, but in his concept this feature is omitted.